Exploring Shared Musical Experiences in Dementia Care: A Worked Example of a Qualitative Systematic Review and Thematic Synthesis. (9th September 2022) - McMahon, Kate; Clark, Imogen N.; Stensæth, Karette; Odell-Miller, Helen; Wosch, Thomas; Bukowska, Anna; Baker, Felicity A.
Qualitative systematic reviews, or qualitative evidence syntheses (QES), are increasingly used in health settings to guide the development of practice and policy. Thematic synthesis is one of the most well-developed approaches used for QES, however there are limited worked examples describing how to apply the steps of analysis in the literature. This paper describes the processes and decisions undertaken in a qualitative systematic review and thematic synthesis from the perspective of a novice researcher. The described review aimed to explore the shared musical experiences of people living with dementia and their family care partners across a range of settings. We found that shared musical activities fostered experiences of connection and wellbeing for people living with dementia and their family care partners. This was demonstrated with moderate-high confidence through six themes, and our findings informed the development of the Contextual Connection Model of Health Musicking. In presenting a worked example of our review, this paper introduces a systematic approach to coding and discusses the complexities of developing and reporting on analytical themes. We identify the need for a specific thematic synthesis reporting tool, and the need to embed reflexive practices into QES tools more broadly.